2000
DOI: 10.1128/iai.68.4.2119-2128.2000
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Mapping of the Outer Membrane Protein P5-Homologous Fimbrin Adhesin of Nontypeable Haemophilus influenzae

Abstract: To identify potential immunodominant and/or adhesin binding domains of the outer membrane protein P5-homologous fimbrin adhesin of nontypeable Haemophilus influenzae (NTHI), three sets of synthetic peptides were synthesized and assayed in an adherence inhibition assay, by Western blotting, and in a biomolecular interaction analysis (BIA) system. The first series of 34 8-to 10-mer peptides represented the entire mature protein sequentially. The second set of four peptides (each 19 to 28 residues) represented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
34
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 59 publications
(53 reference statements)
5
34
0
Order By: Relevance
“…In this study the T cell epitopes of TprK recognized during infection were shown to be limited to regions that are highly conserved among T. pallidum subspecies pallidum isolates, while the B cell epitopes were focused primarily in the variable regions. Our results are consistent with a role for the variable regions in pathogenesis and a functional role for Abs to the variable regions, as seen in other bacterial infections (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…In this study the T cell epitopes of TprK recognized during infection were shown to be limited to regions that are highly conserved among T. pallidum subspecies pallidum isolates, while the B cell epitopes were focused primarily in the variable regions. Our results are consistent with a role for the variable regions in pathogenesis and a functional role for Abs to the variable regions, as seen in other bacterial infections (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionsupporting
confidence: 79%
“…Analogies to other bacteria with molecules that have similar discrete variable regions suggest a possible surface exposure for the variable regions while the conserved regions are intramembrane domains. The discrete variable regions in neisserial Por and Opa, H. influenzae P2 and P5, C. trachomatis MOMP, and B. burgdorferi VlsE are all predicted to be surfaceexposed loops (15,21,22,(25)(26)(27). Under immunological pressure it is advantageous for antigenic targets not essential for structural integrity to be hypermutable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…inhibited the adhesion of M. pneumoniae to host cells to varying degrees. A similar graduation of adhesion inhibition has been observed elsewhere in the investigation of the outer-membrane protein P5-homologous fimbrin adhesin protein from Haemophilus influenzae, in which both short and long peptides covering the protein show differing degrees of inhibition of bacterial adhesion (Novotny et al, 2000). The inhibition region, peptides 4-9, is flanked by the two membrane-associated regions, M4 and M5, in the extracellular D2 region (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…Serum and OMP26 protein and peptide interactions were assessed by SPR using the Biacore 3000 instrument (GE Healthcare Life Sciences, USA) as previously described. 37 The Biacore system measures label-free binding of an analyte from a continuous flow to an immobilized ligand in real time. 38 Changes in refractive index due to variation of the mass on the sensor chip, which results from the interaction of the analyte and ligand, is expressed in relative Resonance Units (RU).…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%